Pertumbuhan Bibit Cabai pada Media Serbuk Gergaji Kayu Sengon dengan Perendaman Air - Rabbani Hario Langgeng; Etik Wukir Tini; Budi Prakoso (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2019)
The purpose of this research was to know the correct soaking period of sawdust media and growth of red chili seedling. This research was conducted at the screen house of the Faculty of Agriculture, University of Jenderal Soedirman, Banyumas, from April-May 2019. The method used was Randomized Completely Block Design. The treatments were consisted of media containing soil, sawdust without soaking, sawdust that has been soaked for 1 day, sawdust that has been soaked for 2 days, sawdust that has been soaked for 3 days, sawdust soaked for 4 days, sawdust that has been soaked for 5 days, sawdust that has been soaked for 6 days, sawdust that has been soaked for 7 days. Observed variables included plant height 14 days, root length, number of leaves, leaf length, leaf width, plant height 42 days. The results showed that germination and growth of seedlings of chili plants on sawdust media that had been soaked for 7 days had better plant height, root length, number and length of leaves than on soil media.